The Efficiency of Liquidity Management in Islamic Banks (Conservative vs. Profit) - Zararee, Abdul Nafea Al; Faris, Jasim Al (Efektywność Zarządzania Płynnością W Bankowości Islamskiej, 2011)
The aim of this paper is to explain and examine the liquidity efficiency in Islamic banks. The paper attempts to bridge the gap in the empirical literature on Islamic banks by building a measurement model to analyze the liquidity efficiency. The measurement of liquidity management efficiency helps planning for liquidity, besides it will help anticipate liquidity needs and build the defensive interval. This procedure will help Islamic banks to identify the exact needs of liquidity for building a profit and to avoid liquidity risk at the same time. The core of the paper is the question of whether liquidity management in Islamic banks is efficient or not, the primary dependent variable is the z-score as a measure of Islamic banks liquidity management soundness.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 158, s. 897-903
Keywords: Islamic banking; liquidity management; efficiency; measure model